2019
DOI: 10.21315/eimj2019.11.1.4
|View full text |Cite
|
Sign up to set email alerts
|

Training Needs Assessment of Academic Teaching Staff in Faculty of Dentistry, University of Gezira, Sudan 2018

Abstract: Training Needs Assessment (TNA) is a triangular term; training (any activities to gain knowledge, skills or change attitude), needs (the gap between current and desired or required) and assessment (process for identifying needs and placing them in priority order). Investment in training of Academic Teaching Staff (ATS) can achieve better performance. TNA is the right step to design an appropriate, cost-effective training programme with clear priorities setting to achieve specific knowledge, skills and practice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 12 publications
1
9
0
2
Order By: Relevance
“… Team/IP Singh, 2015 [ 52 ] India Article (original research) Questionnaire survey / Level VI Nurses, physicians/ Acute care / 274 faculty, senior residents, and nurses Used adapted English TNA tool -Studied at the micro level (tasks/job analysis) nurses’ training needs in a tertiary care specialty hospital in Northern India -TNA identified training needs in patient care, research domain, managerial/administrative domain, and communication domain -Nurses identified their needs relevant to their positions and perceived their performance as higher than physicians Team/IP Tyler & Hicks, 2001 [ 53 ] UK Article (original research) Questionnaire survey / Level VI Nurses / primary healthcare/ 388 family planning nurses Used adapted English TNA tool -The nurse prescribing role was defined primarily in terms of prescribing functions, although advanced professional issues, communication, teamwork and business/administration were also mentioned -Research was not identified as being important -The top 15 training needs included 7 research tasks, advanced clinical activities, applied pharmacology, administration and technical activities Implications: study offers a role definition of the nurse prescriber in family planning, which can help with curriculum planning and CPD programs. Individual Yousif et al, 2018 [ 54 ] Sudan Article (original research) Questionnaire survey / Level VI Other healthcare professionals / school / 29 faculty of Dentistry at University of Gezira in Sudan Used adapted English TNA tool -TNA showed an urgent need for all competencies except three -Priorities for improvement were ranked as follows: research, leadership, health professional education, managerial, community development, teaching and learning skills. -University-level education and development center should focus on emerged training needs of staff Team/IP a Level of evidence appraisal based on the adapted Rating System for the Hierarchy of Evidence [ 21 , 22 ] b Themes: Individual, Team/Interprofessional (IP), Organizational …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“… Team/IP Singh, 2015 [ 52 ] India Article (original research) Questionnaire survey / Level VI Nurses, physicians/ Acute care / 274 faculty, senior residents, and nurses Used adapted English TNA tool -Studied at the micro level (tasks/job analysis) nurses’ training needs in a tertiary care specialty hospital in Northern India -TNA identified training needs in patient care, research domain, managerial/administrative domain, and communication domain -Nurses identified their needs relevant to their positions and perceived their performance as higher than physicians Team/IP Tyler & Hicks, 2001 [ 53 ] UK Article (original research) Questionnaire survey / Level VI Nurses / primary healthcare/ 388 family planning nurses Used adapted English TNA tool -The nurse prescribing role was defined primarily in terms of prescribing functions, although advanced professional issues, communication, teamwork and business/administration were also mentioned -Research was not identified as being important -The top 15 training needs included 7 research tasks, advanced clinical activities, applied pharmacology, administration and technical activities Implications: study offers a role definition of the nurse prescriber in family planning, which can help with curriculum planning and CPD programs. Individual Yousif et al, 2018 [ 54 ] Sudan Article (original research) Questionnaire survey / Level VI Other healthcare professionals / school / 29 faculty of Dentistry at University of Gezira in Sudan Used adapted English TNA tool -TNA showed an urgent need for all competencies except three -Priorities for improvement were ranked as follows: research, leadership, health professional education, managerial, community development, teaching and learning skills. -University-level education and development center should focus on emerged training needs of staff Team/IP a Level of evidence appraisal based on the adapted Rating System for the Hierarchy of Evidence [ 21 , 22 ] b Themes: Individual, Team/Interprofessional (IP), Organizational …”
Section: Resultsmentioning
confidence: 99%
“…A total of 13 articles exhibited the team/IP training needs theme, encompassing more than one professional group or focusing on a team or unit as a whole [ 26 , 28 , 29 , 31 , 34 , 35 , 40 , 45 , 46 , 48 , 51 , 52 , 54 ]. Target populations included nurses, physicians, and other healthcare professionals across acute and primary care, as well as healthcare institutions.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study the validated World Health Organisation (WHO) Hennessey-Hicks TNA survey questionnaire was used to identify the training needs data for health professionals involved in providing oncology services [19]. The questionnaire, is licenced to the World Health Organisation for on-line use, as a toolkit for researchers [20] and has been used in to determine training needs of health professionals in both high and low resource settings [21][22][23][24][25][26]. In this study we set out to determine the training needs of health workers providing comprehensive oncology services in Uganda in a bid to improve cancer care provided to the population they serve.…”
Section: Introductionmentioning
confidence: 99%